Polycomb Group Proteins RING1A and RING1B Regulate the Vegetative Phase Transition in Arabidopsis - Li, Jian; Wang, Zheng; Hu, Yugang; Cao, Ying; Ma, Ligeng (Frontiers in Plant Science, 2017)
Polycomb group (PcG) protein-mediated gene silencing is a major regulatory mechanism in higher eukaryotes that affects gene expression at the transcriptional level. Here, we report that two conserved homologous PcG proteins, RING1A and RING1B (RING1A/B), are required for global H2A monoubiquitination (H2Aub) in Arabidopsis. The mutation of RING1A/B increased the expression of members of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) gene family and caused an early vegetative phase transition. The early vegetative phase transition observed in ring1a ring1b double mutant plants was dependent on an SPL family gene, and the H2Aub status of the chromatin at SPL locus was dependent on RING1A/B. Moreover, mutation in RING1A/B affected the miRNA156a-mediated vegetative phase transition, and RING1A/B and the AGO7-miR390-TAS3 pathway were found to additively regulate this transition in Arabidopsis. Together, our results demonstrate that RING1A/B regulates the vegetative phase transition in Arabidopsis through the repression of SPL family genes.